RETRACTED: Macrozoobenthos of Lakes Beloe and Kolyvanskoe (Northwestern Altai) and the main ecological factors of its formation - Vdovina Olga; Bezmaternykh Dmitry; Sviridov Roman; Lassyi Mikhail (E3S Web of Conferences)
See the retraction notice E3S Web of Conferences 420, 00001 (2023), https://doi.org/10.1051/e3sconf/202342000001